Establishing Halal Lifestyle Term in Clothing: Guideline and Guidance from Islamic Viewpoint - Hasan, Ahmad; Aini, Ahmad (Universiti Malaysia Pahang, 2016)
As halal enters into globalization phases in many parts of the world since the last decade, more people started to show their interests in the concept as well as understanding of halal in their daily living routines. Halal food at the most, extending to clothing and attire, eating out, hotel amenities, house design, banking services, socializing, travelling, toiletries, health and so forth have been occupying interests from manufacturers, customers, stakeholders as well as employers. All these aspects of life are actually inseparable in routine activities of a Muslim. The term ha/al lfts'yle in is yet to commonly establish but had explicitly and implicitly mentioned in the Quran and Hadith as well. Halal should in the end become a privilege for Muslim when halal-oriented goods and services are offered. The paper will present the overview of the term halal lifestyle and will examine specific item in halal lifestyle regarding the personal raiment/attire/dress or similar term as an example. The halal lifestyle in dress will be qualitatively analysed and discussed from halal perspective based on Islamic guidance. Haram clothing lifestyle is also highlighted for better understanding of the halal concept in dressing. Some practical suggestions are included to encourage the gradual establishment of the halal dress lifestyle term.